MENGENAL DIRI MAHASISWA BAHASA PRANCIS MELALUI TIPE BELAJARNYA - IRWANDY IRWANDY (JURNAL TARBIYAH, 2015)
In the process of studying, the most important thing is recognizing the personality. Some people are able to understand an instruction and run it well, by only receiving it. Some people need a memo, and also there are some people who need a demonstration to understand.  Those  happen because of the habit. But, the habit can be improved if we realize and have an intention to learn how to do. Somebody usually use one of their physic capability in understanding the world as his certain perception. Some people may  be able to understand easily by seeing it (visual), some people are by listening to it (auditoria), and some people by movement and touch. Those three types recognized as a system V-A-K (visual-auditoria-kinesthetic). Somebody who recognizes himself well will be easier to learn new things. Therefore, a teacher should recognize firstly the students.